BEAN SPROUT FOR BACTERIAL CELLULOSE PRODUCTION: A REVIEW - Jabosar Ronggur Hamonangan Panjaitan (JITEK (Jurnal Ilmiah Teknosains), 2023)
Cellulose is an organic material that can be obtained from plants and bacterial fermentation. Cellulose which was produced from bacterial fermentation requires some source of nutrients such as carbon and nitrogen. Several studies have been conducted to produce bacterial cellulose (BC) using various nitrogen sources. This paper reviews the production of bacterial cellulose using bean sprouts as a nitrogen source. From the various studies that have been conducted, it was found that the use of bean sprouts as nitrogen source increased bacterial cellulose production. Higher bean sprouts concentration will result in high bacterial cellulose production and thick layer in bacterial cellulose. However, high concentration of bean sprouts can make lower bacterial cellulose production due to increase in the viscosity of fermentation medium and lack of oxygen supply. Based on the organoleptic test, it was found that transparent white bacterial cellulose tends to be produced from high bean sprouts concentrations and is preferred by consumers.